2020
DOI: 10.4081/ozone.2020.9014
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-ozone immunoceutical therapy in COVID-19 outbreak: facts and figures

Abstract: The problems related to the approach to the outbreak of COVID-19 in the world require that all possible effective treatment options be explored. The clinical criterion of the researcher is not to refuse a priori, but to verify and evaluate the proposals that are made. Italian Society of Oxygen Ozone Therapy (SIOOT) proposed to the Italian ISS (Italian Institute of Health) to use oxygen ozone therapy (O2O3) in patients with COVID-19. (...)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 16 publications
1
24
0
2
Order By: Relevance
“…3 Studies have also reported the efficacy and safety of ozone administration on patients of human immunodeficiency virus (HIV), hepatitis C, Ebola, influenza. 3,5,6 As a new immunotherapy and an inexpensive, safe modality, ozone therapy has its rationality in the treatment of COVID-19 patients, 7,8 which was confirmed by our preliminary observational results.…”
Section: Discussionsupporting
confidence: 54%
“…3 Studies have also reported the efficacy and safety of ozone administration on patients of human immunodeficiency virus (HIV), hepatitis C, Ebola, influenza. 3,5,6 As a new immunotherapy and an inexpensive, safe modality, ozone therapy has its rationality in the treatment of COVID-19 patients, 7,8 which was confirmed by our preliminary observational results.…”
Section: Discussionsupporting
confidence: 54%
“…According to literature data, exposure of bacteria, spores and viruses to ozone for only a few minutes causes inactivation [25][26] . Studies by Ricevudi et al 27 proposed oxygen-ozone treatment as a new immunotherapeutic treatment method for the viral agent COVID-19 causing this pandemic and that patients with COVID-19 using this in combination with other treatment methods would benefit from the assisting and synergic effects of ozone therapy. Again, as stated by Ricevudi et al 27 the need for more studies is clear.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Studies by Ricevudi et al 27 proposed oxygen-ozone treatment as a new immunotherapeutic treatment method for the viral agent COVID-19 causing this pandemic and that patients with COVID-19 using this in combination with other treatment methods would benefit from the assisting and synergic effects of ozone therapy. Again, as stated by Ricevudi et al 27 the need for more studies is clear. The bactericidal effect of ozone is linked to attacking the biological material in microorganisms through the oxidation pathway.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important effect of O 3 -AHT in the COVID-19 therapeutical context is the down-regulation action of pyrin domain-containing protein 3 (NLRP3) inflammasome, which is known to play a crucial part in the initiation and continuance of inflammation in various diseases [ 13 ].…”
Section: Introductionmentioning
confidence: 99%